Towards Robot Autonomy in Group Conversations: Understanding the Effects of Body Orientation and Gaze - Vázquez, Marynel; Carter, Elizabeth J.; McDorman, Braden; Forlizzi, Jodi; Steinfeld, Aaron; Hudson, Scott E. (2017 12th ACM/IEEE International Conference on Human-Robot Interaction (HRI, 2017)
We conducted a 2x2 between-subjects experiment to examine the effects of two orientation and two gaze behaviors during group conversations for a mobile, low degree-of-freedom robot. For this experiment, we designed a novel protocol to induce changes in the robot's group and study different social contexts. In addition, we implemented a perception system to track participants and control the robot's orientation and gaze with little human intervention. The results showed that the gaze behaviors under consideration affected the participants' perception of the robot's motion and that its motion affected human perception of its gaze. This mutual dependency implies that robot gaze and body motion must be designed and controlled jointly, rather than independently of each other. Moreover, the orientation behaviors that we studied led to similar feelings of inclusion and sense of belonging to the robot's group, suggesting that both can be primitives for more complex orientation behaviors.